ORGANISATIONAL PERCEPTIONAL IMPERATIVE AND EMPLOYEE ATTITUDE TO WORK IN THE NIGERIA WORKING ENVIRONMENT: A COMPARATIVE STUDY OF PUBLIC AND PRIVATE WORK SITUATION - ODOM, Kenneth Adikeibe; ANUFORO, Robert; OKORIE, Nkechi Fedelia (EBSU Journal of Social Sciences and Humanities, 2024)
The main objective of this study is to ascertain the effects of organizational perceptional imperative on employee attitude to work in the Nigerian work place with a comparative analysis of public and private work situation. The study adopted a survey research design with a population of 212 workers while the sample size was 138 workers randomly selected from 4 enterprises choses among private and public establishments. The study utilized a 15 questionnaire item for it primary data source. The data was analyzed using frequencies and arithmetic mean. To test the hypothesis, the researcher used the Pearson product moment correlation analysis. The data recorded for the research was analyzed employing SPSS version 22. Findings from the study reveals that there is a significant relationship between organizational perceptional imperative and the attitude of work. It was found that most public establishment have a negative perceptional imperative compared to the private enterprises with positive perceptional imperative and this affects workers commitment and job satisfaction. The study recommended among others that Public establishments should devote more time on meeting goals and review its policies on the establishment and management. This will create commitment and job satisfaction among employees.